2008
DOI: 10.1108/14777260810876312
|View full text |Cite
|
Sign up to set email alerts
|

Models of governance and the changing role of the board in the “modernised” UK health sector

Abstract: There is only limited research on the emergent remit, structure or strategy of public sector Boards in the UK, and very limited research on the role of Boards in health care networks: the paper provides some illumination on this limited area of study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 19 publications
(31 reference statements)
1
38
0
Order By: Relevance
“…In these cases 'the powerful influence of the medical staff group diverted the trusts' attention towards meeting their own clinical needs and priorities, at the expense of meeting external performance targets' (p. 436). A study by Addicott (2008) of five cancer network boards also queries the benefits of high clinical representation, with some doctors giving priority to the interests of their own speciality.…”
Section: Literature Reviewmentioning
confidence: 98%
“…In these cases 'the powerful influence of the medical staff group diverted the trusts' attention towards meeting their own clinical needs and priorities, at the expense of meeting external performance targets' (p. 436). A study by Addicott (2008) of five cancer network boards also queries the benefits of high clinical representation, with some doctors giving priority to the interests of their own speciality.…”
Section: Literature Reviewmentioning
confidence: 98%
“…For instance, in a study of the role of the board in the modernised UK Health sector, Addicott (2008) contrasts the traditional model of market-like, top-down driven forceful implementation of strategies with newer governance trends towards collaboration, autonomy and local decision-making. Integration across functions suggests that public governance needs to allow for bridging silos in what is often understood as a 'multi-layered concept with many actors involved' (Stone and Ostrower 2007, 426).…”
Section: Effective Governance Of Not-for-profit Sandt Labsmentioning
confidence: 94%
“…Our proposed typology is constructed by creating a matrix of two key features identified as salient in the literature review and that were found to provide meaning to our data (Langley 1999): (1) funding mechanism (Jackson and Holland 1998;Herman and Renz 2000;Lynn, Heinrich, and Hill 2000;Lynn and Smith 2005) and (2) project interdependence (Crow andBozeman 1998, Stone andOstrower 2007;Addicott 2008) (Figure 1). …”
Section: New Governance Archetypes For Not-for Profit Sandt Labsmentioning
confidence: 99%
“…Addcott explored the role of cancer network boards in London and found limited strategic influence, with constraints due to the continued emphasis of centralised performance management and structural reconfiguration and a resulting confused and conflictual framework (Addcott, 2008). In the school education sector, Farrell found that school governing bodies were not involved in strategic leadership or policy direction, with headteachers more likely to play the lead role in these areas (Farrell, 2005).…”
Section: Roles and Focus Of High Performing Public Sector Boardsmentioning
confidence: 99%